PENGARUH NILAI UTILITARIAN DAN NILAI HEDONIS TERHADAP PERPINDAHAN MEREK DENGAN KEPUASAN KONSUMEN SEBAGAI PEMODERASI (STUDI KASUS PERPINDAHAN MEREK DARI SMARTPHONE LAIN KE IPHONE PADA MAHASISWA DI LINGKUNGAN UNIVERSITAS SYIAH KUALA) - Muhammad Razi Fallefi, M. Ridha Siregar (Departemen Manajemen, 2018)
Abstract: This study aims to determine the effect of Utilitarian Value and Hedonis Value on Brand Transfer With Consumer Satisfaction as Moderator (Case Study of Transfer of Brand from Other Smartphone to Iphone to Student in Environment of Syiah Kuala University). The sample used in this research is 150 respondents who are the perpetrators of brand switching to iphone. Purposive Sampling is used as a sampling technique. Moderate Regression Analysis (MRA) analysis method is used to determine the effect of the variables involved. The results of this study indicate that Utilitarian Value and Hedonic Value Influence on Brand Switching. In addition, the results of the Consumer Satisfaction variables act as quasi moderation on Utilitarian Value variables on Brand Switching, and Consumer Satisfaction plays a role as quasi moderation in Hedonis Value variable on Brand Transfer. The higher the Utilitarian Value and Hedonic Value, The Higher Consumer Satisfaction, the stronger the Brand Switching owned by the consumer.